Carbon hunters pollution, profits, and profiteering - Cernetig, Miro; Wood, Melanie; Force Four Entertainment; Canadian Broadcasting Corporation (Hamilton, NJ : Films for the Humanities & Sciences, 2010)
Examines the status and controversy of the emerging market of the cap-and-trade system for carbon emissions allowances.
Director of photography, Ian Kerr ; editor, Tony Hrkac ; music, Christian Prohom
narrator, Ann-Marie MacDonald
DVD format
Keywords: Carbon offsetting; Emissions trading